Health literacy mediates the effects of educational attainment on online pharmacy navigation skills in older adults with HIV disease. - Matchanova, Anastasia; Sheppard, David P.; Medina, Luis D.; Morgan, Erin E.; Woods, Steven Paul (Psychology & Health, 2023)
ObjectiveThe Internet serves an increasingly critical role in health behaviors for older adults with chronic medical conditions. Guided by theories of health behaviors and literacy, this study examined whether the relationship between educational attainment and online pharmacy skills in older persons with HIV disease (PWH) is mediated by health literacy. Design: Participants included 98 PWH age 50 and older who completed the Test of Online Pharmacy Skills (TOPS), which required them to navigate an experimenter-controlled online pharmacy to perform several naturalistic tasks (e.g., refill an existing prescription). Participants also completed the Medication-Management Test-Revised (MMT-R). Results: Mediation analyses revealed a significant indirect effect of education on both online pharmacy accuracy and MMT-R, which was fully mediated by health literacy. In contrast, there was no direct or indirect effect of education on online pharmacy speed when health literacy was included as a mediator. Conclusion: Health literacy plays an important role in the relationship between years of education attained and the ability of older PWH to successfully navigate online pharmacy tasks and manage their medications. Future studies might examine whether interventions to improve electronic health literacy among older PWH who have lower educational attainment have beneficial effects on online health behaviors.